THE (IN)EFFECTIVENESS OF LAW NO. 1,521/51 IN COMBATING USURY: TENSIONS BETWEEN CRIMINAL CLASSIFICATION AND THE ROLE OF THE NATIONAL FINANCIAL SYSTEM (REMUNOM, 2026)
This Article analyzes the (in)effectiveness of Law No. 1,521/51 in combating usury, focusing on the protection of the popular economy and vulnerable individuals. By criminalizing pecuniary and real usury in Article 4, the statute establishes a penal mechanism aimed at restraining abusive financial practices. However, over time, its application has revealed significant limitations considering contemporary credit dynamics. The interpretation consolidated by Precedent 596 of the Federal Supreme Court excludes financial institutions from the restrictions of Decree No. 22,626/33, thereby allowing the charging of high interest rates within the formal system. The study examines the tension between criminalization, conceived as a blank norm dependent on insufficient regulatory complement, and the regulation of the National Financial System, guided by contractual autonomy and market stability. Law No. 14,905/24 deepens this dissociation by restricting the application of usury limitations in certain contractual relations. The methodology is qualitative, with a deductive approach, based on legislative, jurisprudential, and doctrinal analysis. It is concluded that the practical enforcement of criminal law predominantly affects informal agents, while burdensome practices persist within the formal system, indicating the need for regulatory reform to ensure effective protection of the popular economy.